1996
DOI: 10.1007/bf01211181
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD10/neutral endopeptidase in normal and malignant tissues of the human stomach and colon

Abstract: The expression of common acute lymphoblastic leukemia antigen (CALLA; CD10), which is identical to neutral endopeptidase (NEP, EC3.424.11), was examined in the malignant and adjacent noninvaded tissues of the human stomach and colon (n = 27). All of 27 normal and 18 well or moderately differentiated adenocarcioma tissue specimens were positive for monoclonal antibody (mAb) NL-1 against CD10/NEP, whereas the expression level was clearly decreased in all of 9 specimens of poorly differentiated adenocarcinoma. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
51
1
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 24 publications
1
51
1
1
Order By: Relevance
“…Besides hematopoietic tissue, various benign and malignant nonhematopoietic tissues were also found to express CD10. [5][6][7][8][9][10] CD10 is known to regulate biological activities of peptide substrates by reducing the local concentrations available for receptor binding and signal transduction.…”
mentioning
confidence: 99%
“…Besides hematopoietic tissue, various benign and malignant nonhematopoietic tissues were also found to express CD10. [5][6][7][8][9][10] CD10 is known to regulate biological activities of peptide substrates by reducing the local concentrations available for receptor binding and signal transduction.…”
mentioning
confidence: 99%
“…Sato et al 1 identified a higher expression of CD10 in colorectal carcinomas well or moderately differentiated and a lower expression in poorly differentiated neoplasms. Fujimoto et al 10 observed that the expression of CD10 was higher in well differentiated tumors when compared to the others.…”
Section: Discussionmentioning
confidence: 99%
“…This event is believed to be related to neoplastic progression 2 . Studies have identified a difference in marker expression in tumors and non-neoplastic colorectal mucosa adjacent to the tumor 1,13,14 . Ogawa et al 15 studied the expression of CD10 in tumor tissue of colorectal carcinoma and did not find any expression of this marker in samples of non-neoplastic mucosa adjacent to the tumor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations